Association Between Gender Norms and Experiences of Sexual Violence with Sexual Violence Acts among University of Jember Students - Annisa Nur Fauzia; Elok Permatasari; Ni'mal Baroya (Salasika, 2025)
Sexual violence is a significant problem within university environments, impacting not only the physical and psychological well-being of victims but also deteriorating the overall academic atmosphere. This cross-sectional analytic study aimed to examine the relationship between gender norms, prior experiences of sexual violence, and the perpetration of sexual violence among students at the University of Jember. A total of 176 students participated, selected through stratified proportionate random sampling. Data were collected using structured interviews and analyzed via Chi-square tests with a significance level set at 5%. The findings indicated that students with traditional gender norms, higher semester levels, and previous victimization experiences were significantly more likely to engage in sexual violence behavior. Conversely, no significant relationship was found between gender or age and perpetration. These results emphasize the influence of cultural and social factors on sexual violence behaviors in academic settings. The study recommends implementing educational programs promoting gender equality and providing psychological counseling to support students, particularly those with trauma histories, as effective measures to reduce the incidence of sexual violence on campus.